Vox nostra resonet new music for voices - Vellard, Dominique 1953- (Glossa Music, 2007)
Enth.: Les sept dernières paroles du Christ en croix. Caligaverunt oculi mei. Stabat mater. O vos omnes. Missa laudes Deo.
Interpr.: Ensemble Gilles Binchois. Dir. by Dominique Vellard. - Aufn.: 2003 und 2005